Aplikasi Remote Sensing dan GIS untuk Monitoring Alih Fungsi dan Status Kepemilikan Lahan Sawah di Subak Sanur dan Subak Renon Denpasar - Togatorop, Rico Naris; Lanya, Indayati; Bhayunagiri, Ida Bagus Putu (Agrotrop : Journal on Agriculture Science, 2024)
Remote Sensing and GIS Aplication for Monitoring Conversion and Ownership Status of Rice Fields in Subak Sanur and Subak Renon Denpasar. Subak Sanur and Subak Renon are highly recommended as Sustainable Food Agricultural Land Areas (LP2B). Preparation of LP2B based on Government Regulation (PP) no. 25 of 2012 needs to be equipped with a database, including the Human Resources (HR) database and farmer status. This research aims to create maps of land conversion in 2012, 2018, and 2023, maps of rice field ownership, and a database of farmer human resources in Subak Sanur and Subak Renon. The methods used in this research are literature study, analysis and interpretation of satellite imagery, field surveys, and mapping. Changes in the use of rice fields that occurred in Subak Sanur in the last 10 years (2012-2023) resulted in a conversion of 31.92 ha in Subak Sanur and 53.24 ha in Subak Renon. The total number of farmers in Subak Sanur is 42 people, 37 people have cultivator farming status with a land area of 29 ha and 5 people have owner farmer status with a land area of 4.58 ha. The number of farmers in Subak Renon is 36 people, 32 people have the status of sharecroppers with a land area of 18.63 ha and 4 people have the status of farmer-owners with a land area of 1.71 ha. Farmers in Subak Sanur are dominated by 21 farmers aged 51-60 years and in Subak Renon are dominated by farmers aged 51-70 years, totaling 16 people. It is hoped that the results of this research can be used by the government to support the food balance and provide fertilizer subsidies through the RDKK (Definitive Plan for Farmer Group Needs), The HR (Human Resources) database can be used for agricultural development. The Denpasar City Government needs to make a mayoral regulation as a derivative of Government Regulation 1/2011 and Presidential Decree on land conversion Presidential Decree 59 of 2019 concerning control over land conversion.